Sepuluh Modal Keberhasilan Siswa dalam Memahami Materi Pembelajaran - Yazidul Busthomi; Syamsul A’dlom (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
Subject competency standards can be defined as "statements about knowledge, skills, and attitudes that must be mastered and the level of mastery that is expected to be achieved in learning a subject". The competency standard is a framework that explains the basic development of a structured learning program. The subject competency standard is also the focus of the assessment, so the curriculum development process is the focus of the assessment, although the curriculum contains more of the knowledge, skills, and attitudes document than evidence to show that learners who have learned have early knowledge and skills. Ten modalities for the success of students in understanding learning material are as follows:(1) Students of high intelligence level; (2) Students have motivation in learning; (3)Students are interested in learning; (4) Students attend school; (5) Students are always healthy; (6). Students behave well; (7). Students get attention from their parents; (8) The teacher uses methods that are appropriate for students; (9) The teacher masters the learning strategy; (10) The teacher is professional as a teacher.